2009
DOI: 10.1111/j.1740-0929.2008.00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Goat milk acceptance and promotion methods in Japan: The questionnaire survey to middle class households

Abstract: A consumer questionnaire conducted with the purpose of ascertaining the acceptability of goat milk and related products in Japan was carried out on 345 guarantees of Nippon Veterinary and Life Science University in December 2006. 275 effective responses (79%) representing middle class urban households were returned. The results revealed that (1) 30% of respondents have experienced drinking goat milk and only 10% are aware of the current retail situation of goat milk and related products; (2) over 70% of goat m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 6 publications
1
16
0
1
Order By: Relevance
“…During their stay on the farm, the students were served freshly produced cow's milk at each meal. On the other hand, Ozawa et al (2009Ozawa et al ( , 2010 discussed the possible opportunities for marketing goat milk in Japan. In Japan, the milk that is commonly available to consumers is treated with ultra-high temperature disinfection (accounting for more than 90% of commercial milk, ALIC 1999).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…During their stay on the farm, the students were served freshly produced cow's milk at each meal. On the other hand, Ozawa et al (2009Ozawa et al ( , 2010 discussed the possible opportunities for marketing goat milk in Japan. In Japan, the milk that is commonly available to consumers is treated with ultra-high temperature disinfection (accounting for more than 90% of commercial milk, ALIC 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Milk obtained from several breeds, such as Jersey, Holstein and Guernsey cows, was treated with lowtemperature pasteurization. They reported that more than 70% of the respondents who had never consumed goat milk expressed a desire to try it (Ozawa et al 2009). The cooked odor and taste of milk is different depending on the heat method (Akuzawa 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This happened in the United States and it was a cause of several difficulties for goat breeders who were not able to maintain SCC below the legal limit (Paape et al 2007), even if the milk was obtained from healthy goats. Goat milk is even more used or desired as 'drinking milk' (Ozawa et al 2009), but in pastoral systems, it is mainly transformed into cheese and the composition of raw milk is an important factor in determining the quality of cheese. This research confirmed that in milk from primiparous Sarda goats there are few relationships between TMC and SCC, and showed that milk from local breeds could be considered as a good quality product, despite hand-milking and absence of modern husbandry techniques.…”
Section: Discussionmentioning
confidence: 99%